Multidimensional Symptom Burden among Patients with Hemodialysis in Indonesia - Hinin Wasilah; Dhea Natashia; Chen- Hui Huang; Hsing- Mei Chen; Miaofen Yen (JKP (Jurnal Keperawatan Padjajaran), 2021)
Background: Patients with hemodialysis commonly experience multiple symptoms. Most of the previous studies analyzed the symptoms as one dimension such as the severity dimension. Conducting the comprehensive symptom assessment among patients with hemodialysis is necessary to gain a better understanding of the symptom burden.